Contributions for the optimization of the success management in projects through knowledge management practices- research-in-progress - Takagi, Nilton Hideki (2019)
It is imperative for an organization that its software development projects succeed. However, these projects have often been termed as “problematic endeavors”. This paper presents the preliminary results of a research work conducted to characterize the success of software development projects in Portugal. The results obtained reveal high levels of success, which is contrary to the idea of failure that in the last decades has prevailed. It contributes, therefore, with a new and updated perspective of this phenomenon.